Are rot-causing Botryosphaeriaceae species surviving in healthy Manihot esculenta propagative material in Brazil? - Amanda Cupertino de Queiroz Brito; Juliana Ferreira de Mello; José Vitorino da Silva Neto; Daniele Magna Azevedo de Assis; Ana Elisa de Almeida Souza; Antônio Félix da Costa; Ueder Pedro Lopes; Cristina Maria de Souza‐Motta; Alexandre Reis Machado (2023)
Abstract The study aimed to verify the presence of latent pathogens from the Botryosphaeriaceae family, associated with black root rot and stem dry rot, in healthy propagative material of Manihot esculenta in Brazil. To this end, we investigated the composition of endophytic fungal communities present in fresh healthy stems collected from M. esculenta plantations. Forty-one genera, two families and one subclass of fungi were identified in the collected samples. We detected the species of Botryosphaeriaceae - Lasiodiplodia euphorbiaceicola , L. theobromae and Neoscytalidium dimidiatum - composing fungal endophytic communities in M. esculenta plantations close to the coast of the state of Pernambuco (Brazil). Pathogenicity tests carried out on seedlings and roots of M. esculenta confirmed the capacity of the Botryosphaeriaceae specimens obtained to cause lesions in this host. L. euphorbiaceicola , L. theobromae and N. dimidiatum are recognized as pathogenic for M. esculenta , responsible for causing black root rot and stem dry rot in this crop in Brazil and other countries. However, this is the first study to isolate them as endophytes in healthy propagative material, showing evidence that these Botryosphaeriaceae can survive as pathogens or endophytes in this crop in Brazil.